The News Ecosystem During the Birth of the Confederacy: South Carolina Secession in Southern Newspapers. Issue 2 (2nd April 2020) - Fuhlhage, Michael; Metzger-Riftkin, Jade; Walker, Sarah; Prephan, Nicholas
Abstract : During the secession crisis in 1860–61, the American South was far from unified. Contrary to the idea that the South constituted a single distinct region, this analysis of secession news in Southern newspapers demonstrates the slave states consisted of a constellation of Souths rather than one unified South. Through their decisions about what to print, Southern editors serving unique localities contributed to the social construction of sectionally distinct visions of nationhood. Their decisions about which news and opinion they would reprint and how news was framed made them integral agents in the news ecosystem. This study examines 822 newspaper articles covering secession in the weeks before, during, and after South Carolina's secession in the Charleston Mercury, New Orleans Picayune, Alexandria Gazette, and Macon Telegraph .